Fauna e sazonalidade de flebotomíneos (Diptera: Psychodidae: Phlebotominae) em área de transmissão de leishmaniose na região central do estado do Rio Grande do Sul, Brasil - Osmari, Vanessa (2023)
Sandflies are insects of the Order Diptera, Family Psychodidae and Subfamily Phlebotominae, which include some genera of hematophagous insects capable of transmitting protozoa of the genus Leishmania that cause human visceral leishmaniasis (HVL), canine visceral leishmaniasis (CVL) and American tegumentary leishmaniasis (ATL). . In Santa Maria, in the central region of the state of Rio Grande do Sul (RS), the occurrence of CVL has been recorded since 1985. However, it was from 2017 onwards that there was an increase in the incidence of this disease. In 2021, two autochthonous cases of HVL were recorded, and the municipality started to be considered an area of transmission of the disease. The aim of this study was to identify the vector fauna that may be involved in the transmission of CVL and HVL, in addition to performing molecular tests to detect the presence of Leishmania spp. in insects. For this, from January 2021 to December 2022, modified light traps of the CDC model (Centers for Disease Control) were installed in three neighborhoods of the city, where cases of CVL were previously reported. Of the 89 collections carried out, 119 sand flies belonging to five species were captured: Pintomyia fischeri (76/119, 63.86%), Migonemyia migonei (23/119, 19.33%), Lutzomyia longipalpis (16/119, 13.45%), Brumptomyia sp. (2/119, 1.68%), and Psathyromyia lanei (2/119, 1.68%). Most specimens were captured from February to April 2021 and 2022. All collection points had favorable conditions for encountering sandflies, such as organic matter, shading and an abundant food source. All females were tested by polymerase chain reaction (PCR) and were negative for Leishmania spp. We report for the first time the presence of the main transmitter vector of the agent in the central region of Rio Grande do Sul, Lu. longipalpis, in addition to other species. Although the DNA of Leishmania spp. has not been detected, these results reinforce the need to implement measures to reduce the proliferation of these insects.